Analysis of The Development of A Sustainable Business Model For Horticultural Agriculture : (Study at SMK Negeri 1 Trowulan) - Indah K, Luluk Nur; Imam Mukhlis; Hadi Sumarsono (International journal of technology and education research, 2025)
This study aims to analyze the Development of a Sustainable Business Model for Horticultural Agriculture at SMK Negeri 1 Trowulan. Indonesia has abundant natural resources and high biodiversity. One of the reasons Indonesia is considered an agrarian country is because the agricultural sector is one of the leading sectors in its economy. Vocational education has undergone significant transformation through various episodes of Merdeka Belajar (Freedom to Learn) initiatives launched by the Minister of National Education and Technology Research, Mr. Nadim Makarim. These programs are based on the goal of ‘Link and Match’ between the Business, Industry, and Work World (DUDIKA) and vocational education institutions, including Vocational High Schools (SMK) and Vocational Higher Education Institutions. One of the Merdeka Belajar episodes is the SMK PK (Center of Excellence) program in episode 8. Agribusiness in Food Crops and Horticulture (ATPH) is one of the skill packages at SMK Negeri 1 Trowulan. The ATPH skill package continuously and consistently conducts theoretical and practical learning that creates an engaging learning environment, is favored by students, eagerly awaited hour by hour, and leaves a deep impression on all students. The qualitative research method with a case study approach was chosen because it aligns with the research objective, which is to understand how the sustainable business model for horticultural agriculture is developing at SMKN 1 Trowulan. The school can begin developing more practical marketing systems, such as utilizing online platforms and scaling up commodity production. Students can begin to actively participate in large-scale production development, enabling them to delve deeper into business models for entrepreneurship. This prepares them to engage in agricultural entrepreneurship upon graduation, particularly in horticultural commodities. The strengths and weaknesses of the best strategy for developing student entrepreneurship business models at vocational schools must be considered. Implementing the Business-to-Consumer (B2C) model involves components such as students, schools, partners, communities, and families. Its implementation begins with students learning agricultural practices on a small scale using school land (during the first year of study) with guidance from teachers and partners